The Influence of TikTok Beauty Influencer Credibility on Skincare Product Purchasing Decisions of Indonesian Methodist University Students - Rikshintia Panjaitan; Darwis Robinson Manalu (Takaza Innovatix Labs Ltd., 2026)
The development of TikTok as a digital marketing medium has made beauty influencers one of the main sources of information in skincare product purchasing decisions among students. This study aims to analyze the influence of TikTok beauty influencer credibility on skincare product purchasing decisions among students at Methodist University Indonesia. The study used a quantitative approach with a descriptive and verification survey method. The study population was active students at Methodist University Indonesia who had watched beauty influencer content on TikTok and purchased skincare products based on their recommendations. A sample of 100 respondents was selected using a purposive sampling technique. Data were collected through a questionnaire with a five-point Likert scale, then analyzed using validity tests, reliability tests, descriptive analysis, normality tests, linearity tests, heteroscedasticity tests, and simple linear regression with the help of IBM SPSS Statistics. The results showed that TikTok beauty influencer credibility had a positive and significant effect on skincare product purchasing decisions with a regression coefficient value of 0.511, a significance value of 0.000, and a determination coefficient of 28.3%. This study concludes that the higher the credibility of beauty influencers, reviewed in terms of expertise, trustworthiness, and attractiveness, the higher the decision to purchase skincare products among students at Methodist University of Indonesia.